2020
DOI: 10.2340/16501977-2682
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of power, work and muscle activation during weight-stack and iso-inertial flywheel resistance exercise in young adults with cerebral palsy

Abstract: Cerebral palsy is an umbrella term for a movement disorder in children and adults, which is caused by damage to the immature, developing brain. Individuals with cerebral palsy have weaker, thinner and stiffer muscles compared with individuals without cerebral palsy. Poor muscle function makes everyday activities harder. Efficient training regimes to improve muscle function are therefore needed. This study investigated whether an alternative form of resistance exercise (iso-inertial exercise) was feasible in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The relationship between muscle size and strength, 27 as well as muscle size and running capacity, 9 is well known in typically developing individuals. This association seems to be weaker in individuals with CP because of what seems to be an altered neural drive, causing muscles affected by CP to be underpowered in relation to their muscle size 28 . Notwithstanding, muscle size in individuals with CP has been found to predict maximum voluntary strength 12 and to have a greater impact on the Gross Motor Function Measure than spasticity (modified Ashworth scale rating) 26,29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between muscle size and strength, 27 as well as muscle size and running capacity, 9 is well known in typically developing individuals. This association seems to be weaker in individuals with CP because of what seems to be an altered neural drive, causing muscles affected by CP to be underpowered in relation to their muscle size 28 . Notwithstanding, muscle size in individuals with CP has been found to predict maximum voluntary strength 12 and to have a greater impact on the Gross Motor Function Measure than spasticity (modified Ashworth scale rating) 26,29 .…”
Section: Discussionmentioning
confidence: 99%
“…This association seems to be weaker in individuals with CP because of what seems to be an altered neural drive, causing muscles affected by CP to be underpowered in relation to their muscle size. 28 Notwithstanding, muscle size in individuals with CP has been found to predict maximum voluntary strength 12 and to have a greater impact on the Gross Motor Function Measure than spasticity (modified Ashworth scale rating). 26,29 Supporting the studies highlighting the importance of muscle size in individuals with CP, our result showed that muscle thickness is an essential factor for FR capacity, with the thigh muscle group emerging as somewhat more important than the calf muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, increased collagen ( Booth et al, 2001 ) and intramuscular adipose tissue content ( Noble et al, 2014 ) is believed to contribute to poor muscle function. Individuals with CP respond to exercise, although differences in performance and adaptations exist when compared with TD individuals ( Hjalmarsson et al, 2020 ; von Walden et al, 2020 ). Extracellular vesicle biology has never been investigated in individuals with CP, and it remains to be shown if the response of circulating EVs induced by exercise mimics that of TD individuals.…”
Section: Introductionmentioning
confidence: 99%